Evaluasi Kualitas Air Berdasarkan Parameter Fisik, Kimia, dan Mikrobiologi : Studi Kasus di Lingkungan Produksi PT MBA, Blitar - Nur Agustin Mardiana; Wulan Okta Windari (Universitas Islam Raden Rahmat, Malang, 2024)
PT MBA is an MSME focused on the poultry processing industry, such as duck ungkep and rica-rica. In the production process, the utilization of water in contact with processed food must comply with government regulations. Therefore, water quality testing is conducted based on physical, chemical, and microbiological parameters. The research method adopted was descriptive exploratory. Based on the results of the water sample test in the production room of PT MBA on microbiological parameters, no total coliform and E.coli were found in the sample. Based on the results of water sample tests on physical parameters, namely no abnormal odor and taste, TDS of 27 mg/L. Meanwhile, the chemical parameters are pH 7, nitrate as NO3 dissolved 0.7 mg/L, nitrite as NO2 dissolved 0.05 mg/L, iron (Fe) dissolved 0.05 mg/L, flouride (F) dissolved 0.21 mg/L, hardness (CaCO3) 4 mg/L, chloride 0.096 mg/L, cyanide <0.01 mg/L, and manganese (Mn) dissolved <0.05 mg/L.